Perception of Social Media Use on Home Industry Product Promotion: Expectations-Confirmation Theory (ECT) Perspective - Hasibuan, Anggy Qurnia Raafi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
This study discusses the perception of the use of social media in the promotion of home industry products with the perspective of Expectations Confirmation Theory (ECT). This type of research uses an explanatory research method that explains the causal relationship (cause and effect) to test the hypothesis to explain the relationship and influence between variables. Data collection in this study used a questionnaire instrument using a closed-ended question. The data in this study were analyzed using the smartPLS application. The results showed (1) there was a significant effect of Confirmation on Satisfication, (2) there was a significant positive effect of Service Quality on Satisfication, (3) there was an insignificant effect of Confirmation on Continuance Intention, (4) there was a significant effect of Confirmation on Continuance Intention, (5) there is an insignificant effect of Satisfication on Continuance Intention, (6) there is an insignificant effect of Confirmation on Continuance Intention through Satisfication. Then Continuance Intention will decrease through Satisfication, and Continuance Intention will increase if directly influenced by Confirmation, (7) there is an insignificant effect of Service Quality on Continuance Intention through Satisfication. Then Continuance Intention will decrease through Satisfication. Continuance Intention will increase if directly influenced by Service Quality.